Outcomes in Patients Meeting Cochlear Implant Criteria in Noise but Not in Quiet. Issue 1 (January 2022) - Thai, Anthony; Tran, Emma; Swanson, Austin; Fitzgerald, Matthew B.; Blevins, Nikolas H.; Ma, Yifei; Smith, Michael L.; Larky, Jannine B.; Alyono, Jennifer C.
Abstract : Objective: Evaluate outcomes in cochlear implant (CI) recipients qualifying in AzBio noise but not quiet, and identify factors associated with postimplantation improvement. Study Design: Retrospective cohort study. Setting: Tertiary otology/neurotology clinic. Patients: This study included 212 implanted ears. The noise group comprised 23 ears with preoperative AzBio more than or equal to 40% in quiet and less than or equal to 40% in +10 signal-to-noise ratio (SNR). The quiet group included 189 ears with preoperative AzBio less than 40% in quiet. The two groups displayed similar demographics and device characteristics. Interventions: Cochlear implantation. Main Outcome Measures: AzBio in quiet and noise. Results: Mean AzBio quiet scores improved in both the quiet group (pre-implant: 12.7%, postimplant: 67.2%, p  < 0.001) and noise group (pre-implant: 61.6%, postimplant: 73.8%, p  = 0.04). Mean AzBio +10 SNR also improved in the quiet group (pre-implant: 15.8%, postimplant: 59.3%, p  = 0.001) and noise group (pre-implant: 30.5%, postimplant: 49.1%, p  = 0.01). However, compared with the quiet group, fewer ears in the noise group achieved within-subject improvement in AzBio quiet (≥15% improvement; quiet group: 90.3%, noise group: 43.8%, p  < 0.001) and AzBio +10 SNR (quiet group: 100.0%, noise group: 45.5%, p  < 0.001). Baseline AzBio quiet ( p  < 0.001) and Consonant-Nucleus-Consonant (CNC) scores ( p  = 0.004) were associated with within-subject improvement in AzBio quiet and displayed a higher area under the curve than either aided or unaided pure-tone average (PTA) (both p  = 0.01). Conclusions: CI patients qualifying in noise display significant mean benefit in speech recognition scores but are less likely to benefit compared with those qualifying in quiet. Patients with lower baseline AzBio quiet scores are more likely to display postimplant improvement. Abstract : Supplemental Digital Content is available in the text